Deep acceptor trapping centers in CdI₂-PbI₂ crystal system - Galchynsky, O.V.; Gloskovska, N.V.; Yarytska, L.I. (Functional Materials, 2014)
The model of acceptor trapping centers which consists of Pb³⁺ ion and two atomic I⁰ centers in the temperature range 200-270 K has been suggested. It was constructed on the basis of measurements of thermally stimulated depolarization and spectral sensitivity of photoelectret state in CdI₂ crystals with PbI₂ nanoinclusions.